A Single Dose of Kudzu Extract Reduces Alcohol Consumption in a Binge Drinking Paradigm - Penetar, David M. (Drug Alcohol Depend, 2015)
BACKGROUND: Overconsumption of alcohol has significant negative effects on an individual's health and contributes to an enormous economic impact on society as a whole. Pharmacotherapies to curb excessive drinking are important for treating alcohol use disorders. METHODS: Twenty (20) men participated in a placebo-controlled, double-blind, between subjects design experiment (n=10/group) that tested the effects of kudzu extract (Alkontrol-Herbal™) for its ability to alter alcohol consumption in a natural settings laboratory. A single dose of kudzu extract (2 grams total with an active isoflavone content of 520 mg) or placebo was administered 2.5 hours before the onset of a 90 minute afternoon drinking session during which participants had the opportunity to drink up to 6 beers ad libitum; water and juice were always available as alternative beverages. RESULTS: During the baseline session, the placebo-randomized group consumed 2.7 ± 0.78 beers before treatment and increased consumption to 3.4 ± 1.1 beers after treatment. The kudzu group significantly reduced consumption from 3.0 ± 1.7 at baseline to 1.9 ± 1.3 beers after treatment. The placebo-treated group opened 33 beers during baseline conditions and 38 following treatment whereas the kudzu-treated group opened 32 beers during baseline conditions and only 21 following treatment. Additionally, kudzu-treated participants drank slower. CONCLUSION: This is the first demonstration that a single dose of kudzu extract quickly reduces alcohol consumption in a binge drinking paradigm. These data add to the mounting clinical evidence that kudzu extract may be a safe and effective adjunctive pharmacotherapy for alcohol abuse and dependence.